2007
DOI: 10.1002/jsfa.3077
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus status on Canadian organic farms

Abstract: In eastern North America, many conventional livestock farms, especially dairy farms with high inputs of feed and fertiliser have excess soil phosphorus levels and an annual phosphorus surplus. However, a Canadian dairy farm in transition to organic, without fertiliser inputs reduced its farm P surplus to a marginal level. On long-term organic dairy farms in Ontario, most soils tested low to very low in available P as measured by a standard soil test. Canadian Prairie organic grain farms also consistently demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…In this study we used data sourced from European countries, primarily Germany and Norway, to address the immediate question: What is the soil P status of land under organic management? We used the results of Mallarino et al (2013) and Schick et al (2013) Nutr Cycl Agroecosyst (2018) 110:227-239 229 this analysis to explore the wider question: What factors, including farm type, affect the soil P status on organic farms? We also explored the limitations associated with the use of soil test results to evaluate P status on organic farms.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we used data sourced from European countries, primarily Germany and Norway, to address the immediate question: What is the soil P status of land under organic management? We used the results of Mallarino et al (2013) and Schick et al (2013) Nutr Cycl Agroecosyst (2018) 110:227-239 229 this analysis to explore the wider question: What factors, including farm type, affect the soil P status on organic farms? We also explored the limitations associated with the use of soil test results to evaluate P status on organic farms.…”
Section: Introductionmentioning
confidence: 99%
“…Low soil test P concentrations are common to organic farming systems in Canada (Martin et al 2007;Roberts et al 2008). Chemically untreated phosphate rock (PR) has been proposed as an external input of P in these systems in place of readily soluble synthetic fertilizers that are not permitted under organic production standards.…”
mentioning
confidence: 99%
“…Regardless of rock characteristics, dissolution of PR can be significantly slowed in soils of high pH and high calcium concentration (Bolan et al 1997). The high pH characteristic of most soils under organic production in Canada (Martin et al 2007) poses a significant challenge for the effectiveness of direct applications of PR. However, certain crops that can acidify their rhizosphere have been found to effectively obtain P from PR (Van Ray and Van Diest 1979), even in alkaline soils (Chien et al 2003).…”
mentioning
confidence: 99%
“…(1 in Saskatchewan and Manitoba (Martin et al 2007). Martin et al (2007) also found that the farms that had been managed organically for more than 30 yr had the lowest levels of soil P.…”
mentioning
confidence: 99%